Symbolic computation and satisfiability checking. (September 2020) - Davenport, James H.; England, Matthew; Griggio, Alberto; Sturm, Thomas; Tinelli, Cesare
Abstract: The two communities of Symbolic Computation and Satisfiability Checking have recently found themselves tackling similar problems and having a growing interest in each other's technology. This special issue presents articles whose contribution is of interest to, and is influenced by, both communities. Given the context of this journal we start this editorial with a more thorough overview of Satisfiability Checking, and then turn to Symbolic Computation and the potentials and challenges for collaboration. The collection of articles in this issue is evidence of the already existing fruitful work at the intersection of these communities.